Mono no Aware, Morriña, and Saudade: A Connection Between the Aesthetic Values Drawn from Buddhist Philosophy and the Galician Philosophy of Saudade Expressed Through Playful Writing - Mouriño, Adrián Suárez (Escritura e Imagen, 2025)
The Buddhist philosophy-religion has generated a series of aesthetic values that have spread across various arts and forms of expression, among which one of the most representative is mono no aware. Due to its intrinsic interactive nature, the video game medium allows these principles to be experienced through avatarization and playful writing. This article does not only examine this phenomenon through the analysis of Dark Souls –a work that embodies mono no aware and is used here as an example not because it is unique, but due to its popularity and influence in this regard. The aim of the article is to understand how this Japanese work draws on its national philosophical principles in order to learn how to extrapolate its method to the Galician philosophies of saudade and morriña. From philosophy to playful, meaningful, and interactive writing.
Keywords: mono no aware; saudade; morriña; gemu; videoxogo galego